2021
DOI: 10.46328/aejog.v3i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Experience of our clinic in intrauterine insemination cycles made with microfluidic sperm sorting chips

Abstract: Objective: Determination of the clinical pregnancy rate in intrauterine insemination (IUI) cycles performed with microfluidic sperm sorting chips. Material and Methods: In Giresun University Obstetrics and Pediatrics Hospital Infertility Clinic, 133 patients who underwent IUI after ovarian stimulation with gonadotropins in unexplained infertility, mild to moderate male factor, ovulatory dysfunction, mild endometriosis were retrospectively analyzed between January 2016-January 2020. Microfluidic sperm sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…We estimated miscarriage rates from studies that reported clinical pregnancies, ongoing pregnancies, and live births in three studies [34,41], and in two additional studies [34,41]. We reached out to 21 primary authors to request their raw data [29,34,35,41,44], receiving responses from three [29,39,41].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…We estimated miscarriage rates from studies that reported clinical pregnancies, ongoing pregnancies, and live births in three studies [34,41], and in two additional studies [34,41]. We reached out to 21 primary authors to request their raw data [29,34,35,41,44], receiving responses from three [29,39,41].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…While microfluidics remains the latest development in the analysis and selection of high-quality sperm, with its smallscale size and microenvironment that mimics the mechanisms Processing and selection of healthy sperm is essential for a successful pregnancy and healthy offspring. Sipahi et al [21] , in 133 patients who had undergone IUI with microfluidic sorting, demonstrated that the clinical pregnancy rate was 19.5%, with the highest rate in younger patients. Although not statistically significant, Yaylali and colleagues found the highest clinical pregnancy rate with the use of MSS (22.73%) compared to SWP (15.91%) and the density-gradient (17.39%) methods.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocyst culture has also been used to select the most viable embryos in a cohort, decreasing the number of embryos transplanted and, as a result, decreasing the number of multiple gestations [9]. Microfluidic sperm sorting is a novel method that uses a microfluidic device with four chambers (A, B, C, and D); sperms are put in one chamber and a buffer solution in another, with the sperms traveling through microchannels [10]. The microfluidic device is made of polydimethylsiloxane (PDMS), Pyrex, silicone, quartz, and borosilicate glass.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic sperm sorting is a novel method that uses a microfluidic device with four chambers (A, B, C, and D); sperms are put in one chamber and a buffer solution in another, with the sperms traveling through microchannels [ 10 ]. The microfluidic device is made of polydimethylsiloxane (PDMS), Pyrex, silicone, quartz, and borosilicate glass.…”
Section: Introductionmentioning
confidence: 99%